(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2011)
Key words: Foreign body; collapse consolidation; bronchoscopy DOI: 10.3329/jcmcta.v21i2.7739 Journal of Chittagong Medical College Teachers’ Association 2010: 21(2):47-49